Simeprevir and Sofosbuvir Combination Treatment in a Patient with HCV Cirrhosis and HbS Beta 0-Thalassemia: Efficacy and Safety despite Baseline Hyperbilirubinemia - Nikolaos Papadopoulos; Melanie Deutsch; Athanasios Georgalas; Helias Poulakidas; Lazaros Karnesis (Case Reports in Hematology)
Hyperbilirubinemia is an adverse reaction of simeprevir (SMV). The majority of these patients were taking concurrent ribavirin presenting elevated unconjugated hyperbilirubinemia due to hemolysis. However, cases of hepatic failure with elevated bilirubin level have also been reported in patients with decompensated cirrhosis. We describe a 51-year-old female patient with HbS beta 0-thalassemia and recently diagnosed compensated cirrhosis due to chronic hepatitis C infection. Laboratory evaluation revealed total bilirubin: 2.7 mg/dL and serum HCV-RNA 137.204 IU/mL. HCV was genotyped as 4. A FibroScan revealed 35.3 kPa. She was considered as illegible for pegylated-interferon-free treatment with direct acting antivirals and a course with simeprevir and sofosbuvir (SOF) combination for twelve weeks was planned. Hyperbilirubinemia developed from the beginning with peak values during the 3rd month of treatment. However, no findings of liver decompensation were noticed. Hyperbilirubinemia was benign and fully reversible and our patient finally achieved sustained virological response 24 weeks after the end of treatment.